Impact of socio-economic infrastructure investments on income inequality in Iran - Zolfaghari, Mehdi; Kabiri, Mahbobe; Saadatmanesh, Hamideh (Journal of policy modeling, 2020)
One of the main subjects, governments have been facing is fair distribution of income, and making effort to improve it. In this study, we evaluated the effects of economic (energy, water, ICT) and social (health, education) infrastructure expenses on income inequality in the Iranian provinces for the period of 2007–2016 by the panel corrected standard errors (PCSE) model. The results show that social and economic infrastructures improvements reduce income inequality. However, the magnitude of these effects varies. Investment on education, healthcare, communication technology, energy, and water infrastructures has the greatest impact on income inequality reduction, respectively. Therefore, in order to reduce inequality in deprived areas, combination and optimal allocation of economic and social infrastructures should be considered.